Preparation, characterization, and transfection efficiency of low molecular weight polyethylenimine-based nanoparticles for delivery of the plasmid encoding CD200 gene - Nouri F (Dove Medical Press, 2017)
Fatemeh Nouri,1 Hossein Sadeghpour,2 Reza Heidari,3 Ali Dehshahri,1,4,5 1Department of Pharmaceutical Biotechnology, 2Department of Medicinal Chemistry, 3Department of Pharmacology and Toxicology, School of Pharmacy, 4Center for Nanotechnology in Drug Delivery, School of Pharmacy, 5Pharmaceutical Sciences Research Center, Shiraz University of Medical Sciences, Shiraz, Iran Abstract: Various strategies have been utilized to improve both gene transfer efficiency and cell-induced toxicity of polyethylenimine (PEI), the most extensively investigated cationic polymeric vector. In this study, we sought to enhance transfection efficiency of low molecular weight PEI (LMW PEI) while maintaining its low toxicity by cross-linking LMW PEI via succinic acid linker. These modifications were designed to improve the hydrophilic–hydrophobic balance of the polymer, by enhancing the buffering capacity and maintaining low cytotoxic effects of the final conjugate. Decreased expression of CD200 in the central nervous system has been considered as one of the proposed mechanisms associated with neuroinflammation in multiple sclerosis; therefore, we selected plasmid-encoding CD200 gene for transfection using the modified PEI derivatives. Dynamic light scattering experiments demonstrated that the modified PEIs were able to condense plasmid DNA and form polyplexes with a size of approximately 130 nm. The highest level of CD200 expression was achieved at a carrier to plasmid ratio of 8, where the expression level was increased by 1.5 fold in the SH-SY5Y cell line, an in vitro model of neurodegenerative disorders. Furthermore, the results of in vivo imaging of the LMW PEI-based nanoparticles in the mouse model of multiple sclerosis revealed that fluorescently labeled plasmid encoding CD200 was distributed from the injection site to various tissues and organs including lymph nodes, liver, brain, and finally, kidneys. The nanoparticles also showed the ability to cross the blood–brain barrier and enter the periventricular area. Keywords: polyethylenimine, nanoparticle, transfection, CD200, gene delivery